BUMDES ACCOUNTING WORKSHOP AS AN EFFORT TO IMPROVE BUMDES UNITED ACCOUNTABILITY PANGALENGAN VILLAGE - Yuliafitri, Indri; Kanti, Runita Arum; Fatmawati, Faoziah Ulfa (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2024)
Villages play a key role in economic development at both the regional and national levels. One important initiative to support the village economy is the establishment of Village-Owned Enterprises (BUMDes), which aims to improve village financial accountability and transparency. However, weak accounting and financial reporting systems are often a major challenge. The BUMDes Accounting Workshop conducted in Pangalengan Village aimed to address this issue through Excel application-based accounting training. The results of the activity showed an improved understanding of BUMDes managers on basic accounting principles, good governance, as well as the use of a more efficient accounting information system. The implementation of this system is expected to support the sustainability of village development through more transparent and reliable financial management